Vaginal birth after Cesarean section and levator ani avulsion: a case-control study - Paymova, L; Svabik, K; Neumann, A; Kalis, V; Ismail, K M; Rusavy, Z (Ultrasound in obstetrics & gynecology, 2021)
OBJECTIVE: The aim of this study was to explore the risk of levator ani muscle (LAM) avulsion and enlargement of the levator hiatus following vaginal birth after Cesarean section (VBAC) in comparison with vaginal delivery in primiparous women. METHODS: In this two-center observational case-control study, we identified all women who had a term VBAC for their second delivery at the Departments of Obstetrics and Gynecology at the Faculty of Medicine in Pilsen and the 1st Faculty of Medicine in Prague, Charles University, Czech Republic, between 2012 and 2016. Women with a repeat VBAC, preterm birth or stillbirth were excluded from the study. As a control group, we enrolled a cohort of primiparous women who delivered vaginally during the study period. To increase our control sample, we also invited all primiparous women who delivered vaginally in both participating units between May and June 2019 to participate. All participants were invited for a four-dimensional pelvic floor ultrasound scan to assess LAM trauma. LAM avulsion and the area of the levator hiatus were assessed offline from the stored pelvic floor volumes obtained at rest, during maximum contraction and during Valsalva maneuver. The laterality of the avulsion was also noted. The cohorts were then compared using the χ2 test and Wilcoxon's two-sample test according to the normality of the distribution. P < 0.05 was considered statistically significant. Multivariate regression analysis, controlling for age and body mass index (BMI), was also performed. RESULTS: A total of 356 women had a VBAC for their second delivery during the study period. Of these, 152 (42.7%) attended the ultrasound examination and full data were available for statistical analysis for 141 women. The control group comprised 113 primiparous women. A significant difference was observed between the VBAC group and the control group in age (32.7 vs 30.1 years; P < 0.05), BMI (28.4 vs 27.4 kg/m2 ; P < 0.05) and duration of the first and second stages of labor (293.1 vs 345.9 min; P < 0.05 and 27.6 vs 35.3 min; P < 0.05, respectively) at the time of the index birth. The LAM avulsion rate was significantly higher in the VBAC compared with the control group (32.6% vs 18.6%; P = 0.01). The difference between the groups was observed predominantly in the rate of unilateral avulsion and remained significant after controlling for age and BMI (adjusted odds ratio 2.061 (95% CI, 1.103-3.852)). There was no statistically significant difference in the area of the levator hiatus at rest (12.0 vs 12.6 cm2 ; P = 0.28) or on maximum Valsalva maneuver (18.6 vs 18.7 cm2 ; P = 0.55) between the VBAC and control groups. The incidence of levator hiatal ballooning was comparable between the groups (17.7% and 18.6%; P = 0.86). CONCLUSIONS: VBAC is associated with a significantly higher rate of LAM avulsion than is vaginal birth in nulliparous women. The difference was significant even after controlling for age and BMI. © 2021 International Society of Ultrasound in Obstetrics and Gynecology.
Keywords: Soft Tissue Injuries; Obstetric Labor Complications; vaginal birth after Cesarean; Vaginal Birth after Cesarean; transperineal ultrasound; komplikace porodu; těhotenství; levator ani avulsion; studie případů a kontrol; Adult; anální kanál; ženské pohlaví; ballooning; Humans; Pregnancy; levator hiatus; urogenital hiatus; Ultrasonography, Prenatal; childbirth trauma; VBAC; dospělí; vaginální porod po císařském řezu; Anal Canal; Female; ultrasonografie prenatální; lidé; Case-Control Studies; poranění měkkých tkání